Advancing Knowledge Translation to Improve Inter-Agency Collaboration & Response to Domestic, Sexual, and Gender-Based Abuse - Donnellan, Claudine; Corcoran, Niall; Cannon, Matthew (Journal of Knowledge Management Practice, 2025)
Domestic, sexual, and gender-based abuse (DSGBA) is a complex societal issue with implications for individuals, families, and communities. Recognising the negative implications of agencies developing isolated knowledge bases for service users and society, this Action Research study adopts an integrated knowledge translation approach to investigate the knowledge production and transfer processes among multi-agency practitioners and academics engaged in the DSGBA field. The study introduces a virtual community of practice (vCoP) as a knowledge management system to evaluate its effectiveness in facilitating knowledge translation. Employing a mixed-methods approach, this study aims to contribute a framework for implementing multi-agency vCoP.
Keywords: knowledge management